Brain-Derived Neurotrophic Factor and Its Potential Therapeutic Role in Stroke Comorbidities - Wei Liu; Xiaohui Wang; Margaret O’Connor; Guan Wang; Fang Han (Neural Plasticity)
With the rise in the aging global population, stroke comorbidities have become a serious health threat and a tremendous economic burden on human society. Current therapeutic strategies mainly focus on protecting neurons from cytotoxic damage at the acute phase upon stroke onset, which not only is a difficult way to ameliorate stroke symptoms but also presents a challenge for the patients to receive effective treatment in time. The brain-derived neurotrophic factor (BDNF) is the most abundant neurotrophin in the adult brain, which possesses a remarkable capability to repair brain damage. Recent promising preclinical outcomes have made BDNF a popular late-stage target in the development of novel stroke treatments. In this review, we aim to summarize the latest progress in the understanding of the cellular/molecular mechanisms underlying stroke pathogenesis, current strategies and difficulties in drug development, the mechanism of BDNF action in poststroke neurorehabilitation and neuroplasticity, and recent updates in novel therapeutic methods.